Cleavages, values and the vote in Portugal, 2005-09 - Freire, A. (Portuguese Journal of Social Science, 2013)
Electoral studies remain relatively underdeveloped in Portugal, but there is some consensus about the reduced impact of values on the vote. However, the previousstudies used very limited sets of indicators. Because they included an extensive battery of ‘position issues’, the recent Portuguese National Election Studies,2005–09, allow us to further the debate. Moreover, perhaps because it is embeddedin the cleavage structures, research about the impact of values on the vote is scarcebeyond Portugal. Thus, the present article allows us to integrate the Portuguese caseinto the western debate about the impact of values on the vote: the impact that isembedded in cleavage structures, and the impact that is independent of citizens’ social location. It is shown that by using the appropriate indicators for the positionissues, we find a significant impact of values on the vote: citizens who favour incomeequality, more state intervention and who are more libertarian in their lifestyles arealso more likely to vote for the left; while the opposite trend is true for right-wingvoters. Additionally, we show that only part of the values’ impact on the vote isembedded in the cleavage structure; like in other more advanced polities, a significantpart is not, thus showing that ‘value voting’ is also present and important inthe Portuguese case.